Need for Power among Alcoholic and Nonalcoholic Clergy - Sorensen, Andrew A. (Journal for the scientific study of religion, 1973)
Much of the literature exploring motivation for drinking beverage alcohol asserts that people drink to resolve conflict over dependency wishes or feed their sense of dependency. David McClelland and his associates contend that people drink to make themselves feel more powerful. Two types of need for power are identified: personalized need for power (p-power) and socialized need for power (s-power). McClelland's hypotheses for social drinkers were adapted and tested with 121 Roman Catholic and Episcopal clergymen--65 alcoholics and 56 nonalcoholics. It was found that alcoholics are characterized by p-power and nonalcoholics by s-power or no need for power, regardless of denominational affiliation. Support is offered for the inference that clergy with personalized need for power tend to drink excessively (and later become alcoholics) whereas clergy with socialized need for power or no need for power tend to drink less (and hence are less likely to become alcoholics).